Loss of the Arabidopsis thaliana P4-ATPases ALA6 and ALA7 impairs pollen fitness and alters the pollen tube plasma membrane - McDowell, Stephen C.; López-Marqués, Rosa L.; Cohen, Taylor; Brown, Elizabeth; Rosenberg, Alexa; Palmgren, Michael G.; Harper, Jeffrey F. (Frontiers in Plant Science, 2015)
Members of the P4 subfamily of P-type ATPases are thought to create and maintain lipid asymmetry in biological membranes by flipping specific lipids between membrane leaflets. In Arabidopsis, 7 of the 12 Aminophospholipid ATPase (ALA) family members are expressed in pollen. Here we show that double knockout of ALA6 and ALA7 (ala6/7) results in siliques with a ~2-fold reduction in seed set with a high frequency of empty seed positions near the bottom. Seed set was reduced to near zero when plants were grown under a hot/cold temperature stress. Reciprocal crosses indicate that the ala6/7 reproductive deficiencies are due to a defect related to pollen transmission. In-vitro growth assays provide evidence that that ala6/7 pollen tubes are short and slow, with ~2-fold reductions in both maximal growth rate and overall length relative to wild-type. Outcrosses show that when ala6/7 pollen are in competition with wild-type pollen, they have a near 0% success rate in fertilizing ovules near the bottom of the pistil, consistent with ala6/7 pollen having short and slow growth defects. The ala6/7 phenotypes were rescued by the expression of either an ALA6-YFP or GFP-ALA6 fusion protein, which showed localization to both the plasma membrane and highly-mobile endomembrane structures. A mass spectrometry analysis of mature pollen grains revealed significant differences between ala6/7 and wild-type, both in the relative abundance of lipid classes and in the average number of double bonds present in acyl side chains. A change in the properties of the ala6/7 plasma membrane was also indicated by a ~10-fold reduction of labeling by lipophilic FM-dyes relative to wild-type. Together, these results indicate that ALA6 and ALA7 provide redundant activities that function to directly or indirectly change the distribution and abundance lipids in pollen, and support a model in which ALA6 and ALA7 are critical for pollen fitness under normal and temperature-stress conditions.